A Multivariate Assessment of Age-Related Cognitive Impairment in Octodon degus - Rivera, Daniela S.; Lindsay, Carolina B.; Oliva, Carolina A.; Bozinovic, Francisco; Inestrosa, Nibaldo C. (Frontiers in Integrative Neuroscience, 2021)
Aging is a progressive functional decline characterized by a gradual deterioration in physiological function and behavior. The most important age-related change in cognitive function is decline in cognitive performance (i.e., the processing or transformation of information to make decisions that includes speed of processing, working memory, and learning). The purpose of this study is to outline the changes in age-related cognitive performance (i.e., short-term recognition memory and long-term learning and memory) in long-lived Octodon degus. The strong similarity between degus and humans in social, metabolic, biochemical, and cognitive aspects makes it a unique animal model for exploring the mechanisms underlying the behavioral and cognitive deficits related to natural aging. In this study, we examined young adult female degus (12- and 24-months-old) and aged female degus (38-, 56-, and 75-months-old) that were exposed to a battery of cognitive-behavioral tests. Multivariate analyses of data from the Social Interaction test or Novel Object/Local Recognition (to measure short-term recognition memory), and the Barnes maze test (to measure long-term learning and memory) revealed a consistent pattern. Young animals formed a separate group of aged degus for both short- and long-term memories. The association between the first component of the principal component analysis (PCA) from short-term memory with the first component of the PCA from long-term memory showed a significant negative correlation. This suggests age-dependent differences in both memories, with the aged degus having higher values of long-term memory ability but poor short-term recognition memory, whereas in the young degus an opposite pattern was found. Approximately 5% of the young and 80% of the aged degus showed an impaired short-term recognition memory; whereas for long-term memory about 32% of the young degus and 57% of the aged degus showed decreased performance on the Barnes maze test. Throughout this study, we outlined age-dependent cognitive performance decline during natural aging in degus. Moreover, we also demonstrated that the use of a multivariate approach let us explore and visualize complex behavioral variables, and identified specific behavioral patterns that allowed us to make powerful conclusions that will facilitate further the study on the biology of aging. In addition, this study could help predict the onset of the aging process based on behavioral performance.